The internationalisation of antitrust policy - Dabbah, Maher M. (Cambridge University Press, 2003)
Dabbah's clear and original discussion of the internationalisation of antitrust policy examines in particular the decisional practice of relevant bodies in the EC and the US. He concludes by predicting future developments. This will interest antitrust officials, international organisations, businesspeople, academics, researchers and policy-makers involved in antitrust law and policy.